Factors influencing leisure walking in residential areas in a city in Iran - Aliyas, Zeinab (2017)
Walkability has become increasingly prevalent in the city planning and public health fields. Although many researchers investigated the factors that influence walkability of neighborhoods but understanding how people are encouraged to do more walking activity with different purposes in the neighborhoods remains uncertain. Bandar Abbas is a fast developing city, thus the changing condition of the city has witnessed residential developments that prioritize vehicle rather than pedestrian. Therefore the walk paths and public parks have not been designed to support walking and pedestrian activities. The current study aimed to determine why residents are discouraged walk leisurely in neighborhoods and which factors strongly influence the walkability of the neighborhoods related to leisure walking. In this regards the walkability of neighborhoods and the environmental characteristics related to leisure walking including neighborhood safety, quality of parks and aesthetics of neighborhoods were examined to determine the influencing factors and concerns of residents in relation to leisure walking activity. Four neighborhoods of Bandar Abbas in Iran were selected as sample areas to examine the issues concerned. The study adopted a mixed method strategy to address the research inquiries and to draw conclusions from the analyses. Firstly, the structured observations were performed to assess the physical condition of neighborhoods in light of leisure walking needs and benefits. After that a sample of 500 residents from four residential neighborhoods of the city were selected to respond to the structured questionnaire. The objective is to identify the neighborhoods’ walkability characteristics and and factors that influence pattern of leisure walking. The quantitative data from the survey was analyzed using SPSS and Smart-PLS software and the observation data was used to validate the survey results. The findings of the study revealed a strong correlation between pattern of leisure walking and neighborhood safety while the functions of neighborhood parks influence pattern of leisure walking activity. Presence of walking trail, size, proximity and safety of parks were identified as essential factors in deciding where to do exercise walking, besides the socio-demographic factors had a significant influence on choosing the parks for recreational walking. Finally, neighborhood safety was discovered to be most strongly associated with the pattern of leisure walking rather than quality of neighborhood parks and aesthetics of neighborhoods.